Common Woody Plants of Florida Scrub Ecosystems - Lynn Proenza; Michael Andreu (EDIS)
The purpose of this fact sheet is to help identify a few of the more common woody plant species found in Florida’s scrub ecosystems. In the individual plant descriptions, words that appear in bold font are considered to be key field characteristics that will aid in identification of the species. This 14-page fact sheet was written by Lynn Proenza and Michael Andreu and published by the UF Department of School of Forest Resources and Conservation, October 2012.